Ranggawarsita dan Sufisme Jawa: Studi Pemikiran Bagus Burham Terhadap Budaya Islam Jawa (1823-1870) - Samudra Eka Cipta (LPPM Institut Pesantren KH. Abdul Chalim, 2020)
This research is explained about Raden Ngabehi Ranggawarchitecture in the history of Javanese literature and good Burham (another name of rangawarchitecture related to the development of Theosufism teaching in Java). This research uses several problems, namely 1) how the history of Rangawarchitecture as a Javanese literary? 2) How is Javanese literary condition in the 19th century? 3) How ranggawarchitecture thought against Islam. This study used a historical approach by looking at a barrage of historical events and using a literature study approach.